Hydrological Analysis of Wadi Badush basin using (GIS) - AL-Jboory, Sundas Jumaa Hussein; Al-Naish, Fawaz Hameed Hamo (Al-Adab Journal, 2021)
Hydro morphometric studies are one of the main and recent trends in the study of river basins which is concerned with the quantitative (numerical) analysis of the characteristics of the land shape and finding the mathematical relationships that link the topography and water drainage networks. The study aims to use the GIS technology to reveal the hydrological characteristics of the Badush Valley Basin and the secondary valleys, which are represented by the spatial, morphological and topographic characteristics and the characteristics of the drainage network, as well as the drainage patterns to build a digital geographic information base for the basin. The study relied on finding the hydro morphometric characteristics of the secondary basins of the Badush Valley Basin based on the Digital Elevation Model (DEM) and using the Arc Map program in the Arc GIS v.10.8 system, and the analytical approach was followed for the valleys of the study area, and the method Quantitative, which aims to apply quantitative criteria and standards in the analysis of hydrological processes, and a map of the river network was produced, which was classified according to the Streller method into its river levels for the basin of the study area. The total area of the basin reached (329.95 km2), and the number of river ranks reached six river levels. The network of waterways varied in their numbers and lengths according to their ranks and lengths, While the total network of waterways is (734), and its total lengths were (711.06) km, and its lengths are due to the discrepancy in the processes of its formation and emergence, as well as the variance in the terrain characteristics of the Badush Valley Basin.